2011
DOI: 10.1016/j.jcrs.2011.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different acrylic intraocular lens materials on optical quality of vision in pseudophakic eyes

Abstract: Hydrophobic acrylic IOLs gave better low contrast visual acuity. Even within the acrylic subgroup, the optical quality varied significantly. The IOL material is an important factor influencing the optical quality of vision with different acrylic IOLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
4
1
Order By: Relevance
“…Several studies have previously documented mean OSI with monofocal AcrySof IOLs at different postoperative follow-up periods, ranging from 1.38 at 3 months to 1.8 at nearly 1 year postoperatively 2,5,10. In the current study, the OSI values for eyes implanted with monofocal AcrySof IOLs were higher than previously reported: 2.01 at a mean of 57 months, with some patients followed for up to 10 years.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Several studies have previously documented mean OSI with monofocal AcrySof IOLs at different postoperative follow-up periods, ranging from 1.38 at 3 months to 1.8 at nearly 1 year postoperatively 2,5,10. In the current study, the OSI values for eyes implanted with monofocal AcrySof IOLs were higher than previously reported: 2.01 at a mean of 57 months, with some patients followed for up to 10 years.…”
Section: Discussioncontrasting
confidence: 57%
“…Nanavaty et al found comparatively higher mean OSI for hydrophilic (2.2–2.7) vs hydrophobic acrylic IOLs (1.6–1.8) 3 months postoperatively 10. Higher OSI values have been observed for multifocal IOLs1,3 than for monofocal IOLs of the same material 2…”
Section: Introductionmentioning
confidence: 98%
“…The AcrySof IOL platform has known low rates of PCO, which are attributed in part to the square posterior optic edge and material properties. 1,18–20 The 1-year Nd:YAG rate in this study was 1.5% vs 2.2% with a similar AcrySof trial. 5 This study shows that the frequency of PCO at 3 years for Clareon remained very low, with 92.9% of eyes having either no PCO or clinically nonsignificant PCO.…”
Section: Discussionsupporting
confidence: 50%
“…[21][22][23] In addition to reducing PCO, the precision optic edge of Clareon has been designed to reduce edge-glare photic phenomena and epithelial cell migration onto the posterior capsule. 1,17,20 In vitro, the Clareon IOL had negligible peripheral glare compared with other hydrophobic IOLs with different designs. 24 In a recent preclinical study, a second experimental model was developed that represents reflected and transmitted IOL glare.…”
Section: Discussionmentioning
confidence: 99%
“…It is now known that quality of vision can be influenced by IOL material. 16 A detailed objective assessment of quality of vision in these studies is discussed in our previous publication. 16 This study focused on the comparison of various IOLs with different asphericity profiles, and quality of vision assessment was not part of this project.…”
Section: Discussionmentioning
confidence: 99%